Systematic Literature Review: Pendidikan Karakter Di Sekolah Dasar - Elfa Sri Surya Ulfa; Sahrun Nisa; Ari Suriani (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The moral crises that develops in schools makes character education more crucial.The literature study method with systematic review (SR) is a systematic strategy used in this study to gather, evaluate critically, integrate, and compile the findings of multiple research papers on research issues or subjects that require additional investigation. The research findings from the eight aforementioned publications demonstrate the importance of implementing character education in elementary schools and its potential to significantly impact students' daily lives and educational processes. Character education strives to raise students' overall, integrated, and balanced moral development in compliance with each educational institution's competency standards.